Ecological consumer neuroscience for competitive advantage and business or organizational differentiation - Antonio González-Morales; Jelena Mitrovic; Rafael Ceballos Garcia (European Research on Management and Business Economics (ERMBE), 2020)
The importance of branding in marketing strategies makes it essential to understand the elements that give value-added to the brands. The very nature of ecological brands adds value to them. Knowing the underlying emotions of the elements that add value to brands can justify the benefit of applying neuromarketing to branding. The objective of this study is to justify the use of neuromarketing tools in the ecological branding strategy by analysing the existing literature on branding, ecological branding and neuromarketing. The existing relationship between the elements that give value-added to the brand and the emotional variables that neuromarketing measures, justifies the use of neuromarketing tools in the ecological branding strategy.
Keywords: M1; M3; 650; Ecological branding; Neurobranding; Neuromarketing